Postnatal Steroids Use for Bronchopulmonary Dysplasia in a Quaternary Care NICU - Kanagaraj, Uthayakumaran; Tan, Jason; Soraisham, Amuchou; Lodha, Abhay; Shah, Prakesh; Kulkarni, Tapas; Shivananda, Sandesh (American Journal of Perinatology, 2024)
Objective Intercenter variation and trends in postnatal steroids (PNS) use among preterm infants for prevention or treatment of bronchopulmonary dysplasia (BPD) is known. Understanding intracenter PNS use patterns facilitate implementation of center-specific change interventions to optimize outcomes.This study aimed to (i) quantify the proportion of infants who received PNS, and describe the timing, type, trends over time, regimen used, and deviations, and (2) describe the clinical characteristics and unadjusted outcomes of infants who received PNS.Study Design This was a cohort study in a quaternary neonatal intensive care unit including infants born at less than 33 weeks, and who received PNS for prevention or treatment of BPD between 2011 and 2021. Following data were included: proportion of babies who received PNS; type of PNS; age at initiation and duration; trends over time; deviation from published regimen; morbidity, mortality, and cointerventions.Results One hundred and eighty four infants (8% of <33 week' infants) received PNS. The median (interquartile range [IQR]) gestational age and birth weight were 25 (24–26) weeks and 720 (625–841) grams, respectively. The median (IQR) day of initiation and duration of PNS use were 29 (19–38) and 10 (10–22) days, respectively. One hundred and fifty-seven (85%) infants received dexamethasone (DX) and 22 (12%) received hydrocortisone as the first PNS course, and 71 (39%) infants received multiple courses. The proportion of infants receiving PNS remained unchanged, but the cumulative median dose received for BPD per patient increased by 56%. Nearly one-third of cumulative PNS dose came from PNS used for non-BPD indications. Forty-six percent infants had a deviation from published regimen (±20% deviation in duration or ±10% deviation in dose). Survival, survival without major morbidity, moderate-to-severe BPD, and technology dependence at discharge were 87, 2, 91, and 67%, respectively.Conclusion Increased variation in PNS use, deviation from published regimen, and concurrent PNS exposure from non-BPD indication offer insights into implementing interventions to improve processes.Key Points
Keywords: bronchopulmonary dysplasia; postnatal steroids; neonatal intensive care; variation